(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with Simulation centers at educational institutions and professional development institutions of the Ministries of Emergency Situations, Health and Other Ministries of the Republic of Uzbekistan, as well as some types of modern interactive simulators and simulators available in them, and the interactive simulator “MKP-02/OG”, which is an effective means of teaching in work on improving the knowledge and skills of the personnel of fire and rescue units.